2012
DOI: 10.1371/journal.pone.0040589
|View full text |Cite
|
Sign up to set email alerts
|

Acute Podocyte Vascular Endothelial Growth Factor (VEGF-A) Knockdown Disrupts alphaVbeta3 Integrin Signaling in the Glomerulus

Abstract: Podocyte or endothelial cell VEGF-A knockout causes thrombotic microangiopathy in adult mice. To study the mechanism involved in acute and local injury caused by low podocyte VEGF-A we developed an inducible, podocyte-specific VEGF-A knockdown mouse, and we generated an immortalized podocyte cell line (VEGFKD) that downregulates VEGF-A upon doxycycline exposure. Tet-O-siVEGF:podocin-rtTA mice express VEGF shRNA in podocytes in a doxycycline-regulated manner, decreasing VEGF-A mRNA and VEGF-A protein levels in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
73
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(79 citation statements)
references
References 50 publications
4
73
0
2
Order By: Relevance
“…While mesangial cells are well known to produce fibronectin by various stimuli (53,54), recent studies showed that podocytes can also produce fibronectin, transforming growth factor-␤, angiotensin II, and high glucose upregulated fibronectin in cultured podocytes (25,34,39,55). Upregulation of the extracellular matrixes was also observed without clear evidence of podocytopenia in adriamycin nephropathy (19) or in a model of diabetic nephropathy (12), and fibronectin staining overlapped, at least partially, with nephrin in the mouse kidney consistent with fibronectin production by podocytes in addition to mesangial cells (70). Furthermore, some investigators propose that podocytes may undergo epithelialmesenchymal transition when the injury is progressive to escape from apoptotic cell death and that the associated phenotypic changes may contribute to impaired permselectivity (42).…”
mentioning
confidence: 78%
“…While mesangial cells are well known to produce fibronectin by various stimuli (53,54), recent studies showed that podocytes can also produce fibronectin, transforming growth factor-␤, angiotensin II, and high glucose upregulated fibronectin in cultured podocytes (25,34,39,55). Upregulation of the extracellular matrixes was also observed without clear evidence of podocytopenia in adriamycin nephropathy (19) or in a model of diabetic nephropathy (12), and fibronectin staining overlapped, at least partially, with nephrin in the mouse kidney consistent with fibronectin production by podocytes in addition to mesangial cells (70). Furthermore, some investigators propose that podocytes may undergo epithelialmesenchymal transition when the injury is progressive to escape from apoptotic cell death and that the associated phenotypic changes may contribute to impaired permselectivity (42).…”
mentioning
confidence: 78%
“…11 These properties of ELP-VEGF may have extended the time for VEGF to bind to its receptors widely distributed in vascular endothelial cells, glomerular cells, and podocytes, 32,39 and amplified autocrine/ paracrine actions of VEGF in the kidney, 40,41 as in turn may explain the superior efficacy over unconjugated VEGF therapy. However, a potential limitation of our study may be that the model may represent an early stage of RVD and that only one time-point was evaluated, since RVD in humans is a slowly progressive disease and intrinsic kidney damage develops over months and years.…”
Section: Discussionmentioning
confidence: 99%
“…The role of podocyte VEGF-A in regulating α V β 3 integrin signaling in the mouse GBM has been shown in vivo [47]. α V β 3 integrin plays an important role in angiogenesis and in hypertension-induced vascular remodeling in the kidney.…”
Section: Podocyte-endothelial Cell Link and Vascular Endothelial Growmentioning
confidence: 99%